Healthcare supply chain management: Macro and micro perspectives - Duangpun Kritchanchai (2020)
© Wyższa Szkoła Logistyki, Poznań, Polska. Background: The concept of supply chain management is to coordinate and collaborate among supply chain players in order to achieve system efficiency. Supply chain coordination and collaborations deal with the connection of operations throughout the chain with material and information flowing smoothly across these supply chain operations in achieving efficiency. Healthcare supply chain is one of such complex systems involving many stakeholders in the supply chain. Coordinating a single platform for these stakeholders is a challenge by achieving smooth flow of operations on this platform. Therefore, the purpose of this paper is to explore the operations in this healthcare supply chain materials and information flows across the players at two levels, macro and micro perspective. Methods: The supply chain infrastructure enabling efficiency is investigated in the hospital environment. Multiple case studies have been conducted at 13 hospitals which include secondary hospitals and primary hospitals. Triangulation techniques, including interviews, site visiting and document analysis, are employed for data collection so as to enhance reliability and validity of the study. Results and conclusions: The study found that the healthcare supply chain efficiency could be achieved at 2 levels, namely supply chain level and firm level. The main concerns of the organizations of both levels are process efficiency and patient safety.